2020
DOI: 10.3389/fneur.2020.573718
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Non-invasive Neuromodulation for the Management of Disorders Related to COVID-19

Abstract: Background: Novel coronavirus disease (COVID-19) morbidity is not restricted to the respiratory system, but also affects the nervous system. Non-invasive neuromodulation may be useful in the treatment of the disorders associated with COVID-19.Objective: To describe the rationale and empirical basis of the use of non-invasive neuromodulation in the management of patients with COVID-10 and related disorders.Methods: We summarize COVID-19 pathophysiology with emphasis of direct neuroinvasiveness, neuroimmune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 226 publications
(266 reference statements)
0
40
0
Order By: Relevance
“…Therefore, activation of the NTS and the cholinergic anti-inflammatory pathway, both pharmacologically, by activating the alpha 7 nicotinic receptors, and electrically, through noninvasive brain neuromodulation and vagus nerve stimulation (VNS), as also suggested by Baptista et al [39], appear to be promising therapeutic strategies to balance the ANS and produce a balanced autonomic response [40][41][42]. Besides, Leitzke et al [43] have recently reported that these therapeutic approaches for sympathovagal balance in severe courses of COVID-19 can be achieved diagnostically by measuring HRV.…”
Section: Implications and Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…Therefore, activation of the NTS and the cholinergic anti-inflammatory pathway, both pharmacologically, by activating the alpha 7 nicotinic receptors, and electrically, through noninvasive brain neuromodulation and vagus nerve stimulation (VNS), as also suggested by Baptista et al [39], appear to be promising therapeutic strategies to balance the ANS and produce a balanced autonomic response [40][41][42]. Besides, Leitzke et al [43] have recently reported that these therapeutic approaches for sympathovagal balance in severe courses of COVID-19 can be achieved diagnostically by measuring HRV.…”
Section: Implications and Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…It has been hypothesized that SARS‐CoV‐2 could invade the CNS through the circulation, cerebral spinal fluid or via cranial nerves/olfactory bulb, by synapse‐connection or by direct endocytic paths (similar to ZIKA virus) (Baptista et al., 2020; Channappanavar & Perlman, 2017). Indeed, COVID‐19 is capable to invade astrocytes, neuroblasts, and neurons via the direct binding to the ACE2 receptor (Baptista et al., 2020). This would lead to the dysfunction of ACE2‐mediated cascades with potential implications in neuroinflammation, neurodegeneration, and neurotoxicity processes.…”
Section: Discussionmentioning
confidence: 99%
“…3. Non-invasive brain stimulation (NIBS), including transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) (Baptista et al 2020;Shinjo et al 2020). tDCS is an experimental NIBS technique, which involves placing two electrodes over the head and running a low intensity current between them to either stimulate (anodal) or inhibit (cathodal) neuronal activity.…”
Section: D)mentioning
confidence: 99%